Analysis of Student Needs in Electrochemistry Learning Based on Culturally Responsive Transformative Teaching (CRTT) in Grade XII MIPA UM Laboratory High School - Widarti, Hayuni Retno; Sulistyorini, Dwi; Sumarsono, Raden Bambang; Setyowati, Istri; Rokhim, Deni Ainur; Juliandani, Fasha; Marestya, Alfina Dwi (JCER (Journal of Chemistry Education Research), 2025)
This study aims to analyze students’ learning needs in electrochemistry learning based on the Culturally Responsive Transformative Teaching (CRTT) framework. CRTT is a pedagogical approach that integrates students’ cultural backgrounds and lived experiences into learning to make it more inclusive and meaningful. The research employed a descriptive quantitative method complemented by qualitative data from open responses. A total of 32 Grade XII MIPA students from UM Laboratory High School participated in the study. Data were collected through a validated questionnaire consisting of 15 closed and 5 open-ended items. The results show that 64% of students have a moderate understanding of electrochemistry, with the most difficult subtopics being Galvanic and Electrolysis Cells. Students expressed strong interest (80%) in contextual learning through simple and eco-friendly edukits, as well as enthusiasm for integrating local culture such as keris plating and natural electrolytes from plants. These findings emphasize the importance of developing CRTT-based learning tools that connect chemical concepts with students’ cultural realities to foster deeper conceptual understanding, engagement, and transformative learning experiences.